A semantic robotic grasping framework based on multi-task learning in stacking scenes. (May 2023) - Duan, Shengqi; Tian, Guohui; Wang, Zhongli; Liu, Shaopeng; Feng, Chenrui
Abstract: Autonomous robotic grasping is an essential skill for service robots to perform specified tasks in unstructured scenarios. Previous work focus on simple pick-and-place tasks, and it is not satisfactory for real-world scenes that have requirements for manipulation. In this paper, we present a modular intelligent robot architecture via multi-task convolutional neural network which can be used for specific object grasping and manipulation in a stacked and cluttered environment. Firstly, an end-to-end, multi-task semantic grasping convolutional neural network (MSG-ConvNet) that simultaneously outputs the results of grasp detection and semantic segmentation is proposed to recognize the affiliations between objects and grasps in cluttered scenarios. Secondly, we propose a post-processing method which allows the robot to select an optimal grasping area in an active perception way through simply reasoning on the multi-modal information output by the proposed model. The proposed multi-task network has a great improvement in both recognition accuracy and detection speed on the public multi-object dataset GraspNet-1Billion compared with the benchmark. The proposed grasp detection method also yields state-of-the-art performance with accuracies of 95.06% and 98.6% on the public single-object Jacquard Dataset and Cornell Dataset, respectively. In addition, the experiments in a real-world scene demonstrate that our proposed method has stronger robustness and adaptability than the simple direct grasping strategy in the environment with higher mutual occlusion.